2016
DOI: 10.1371/journal.pntd.0004989
|View full text |Cite
|
Sign up to set email alerts
|

Succinyl-CoA Synthetase: New Antigen Candidate of Bartonella bacilliformis

Abstract: BackgroundBartonella bacilliformis is the causative agent of Carrion’s disease, a neglected illness with mortality rates of 40–85% in the absence of treatment. The lack of a diagnostic technique to overcome misdiagnosis and treat asymptomatic carriers is of note. This study aimed to identify new B. bacilliformis antigenic candidates that could lead to a new diagnostic tool able to be implemented in endemic rural areas.Methodology/Principal FindingsBlood (n = 198) and serum (n = 177) samples were collected in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 26 publications
0
57
1
2
Order By: Relevance
“…3 There are around 40-50% of asymptomatic carriers in endemic areas who, in the absence of an animal reservoir, are considered the perpetuators of the disease. 5 Peru has endemic areas with approximately 1.7 million atrisk inhabitants. [1][2][3] Moreover, in the last few years, an expansion of this disease toward new areas has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…3 There are around 40-50% of asymptomatic carriers in endemic areas who, in the absence of an animal reservoir, are considered the perpetuators of the disease. 5 Peru has endemic areas with approximately 1.7 million atrisk inhabitants. [1][2][3] Moreover, in the last few years, an expansion of this disease toward new areas has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ellis et al reported a case-control study during an outbreak of acute bartonellosis in the Urubamba Valley (Cusco department) in 1998 (37), and more recently, Sánchez Clemente et al (28) described a 2003 outbreak in Caraz (an area of endemicity in the Ancash department). In 2013 to 2014, 428 cases were reported in the Piura department, with an outbreak in the Lalaquiz district (44,50,51). Finally, in 2016, 33% of the total number of cases were reported in Huanuco (52).…”
Section: Fig 2 Legend (Continued)mentioning
confidence: 99%
“…Thus, it was estimated that the negative net migration rate of Peruvian inhabitants to other countries in the period 1990 to 2012 was Ͼ2.5 million, with the number of Ecuadorian people living in other countries in 2008 also being around 2.5 million (http://www.migracionoea.org/index.php/es/parte-iii-informes-por-pais.html) (65). This and the high prevalence of carriers in areas of endemicity (50), together with the periodic visits of emigrants to related areas of endemicity and the possible long duration of asymptomatic infections (50,62), underline the undoubtable presence of asymptomatic carriers in countries where the disease is not endemic.…”
Section: Carrion's Disease Outside Perumentioning
confidence: 99%
See 2 more Smart Citations